Eksplorasi Hadis dan Al-Qur’an Qs. Al-Isra' Ayat 82 Tentang Manfaat Kesehatan dalam Perspektif Hijamah - Khoerunnisa, Atikah; Alif, Muhammad (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2025)
Hijamah, or wet cupping therapy, is a well-known medical practice deeply rooted in Islamic tradition, with profound historical origins in the hadiths of Prophet Muhammad (peace be upon him). Research on hijamah often integrates both medical and spiritual aspects, and in this context, the exploration of hadith plays a crucial role in understanding the practice's foundation and legitimacy. This study aims to explore the hadiths and the Qur'an related to hijamah, and to analyze their relevance and application in the context of modern medicine. The hadiths discussing hijamah include recommendations and praise for this practice, as reported in various hadith collections such as Sahih al-Bukhari and Sahih Muslim. This research employs a qualitative approach using thematic hadith analysis and grounded theory. The analysis results indicate that hijamah receives significant recognition in Islamic tradition as a recommended therapeutic practice, with many hadiths reflecting its blessings and efficacy. This study concludes that while there is a strong basis for hijamah in Islamic tradition, further research is needed to assess the suitability of this practice within the context of modern medicine. The exploration of hadith and the Qur'an provides important insights into the historical and spiritual perspectives of hijamah, but integration with objective medical research is key to scientifically validating its benefits. The findings of this study are expected to provide insights into how Islam utilizes this cupping therapy and how a Muslim should approach it. The research findings can serve as a moral guide and teach the importance of balance, cleanliness, and commitment to religious teachings, all of which contribute to achieving a social status aligned with Islamic values.